Digital Tools for the Morphological Design of the Naturally Ventilated Buildings: Case study: analysis of the wind driven ventilation potential of linear isolated blocks. Issue 1 (26th January 2018) - Ferrucci, Margherita; Brocato, Maurizio; Peron, Fabio
Naturally ventilated buildings have great potential in terms of comfort and energy saving. However their design is difficult, as the effectiveness of the ventilation is affected by many parameters. Through a parametric CFD (Computational Fluid Dynamics) simulations, graphical tools are generated to evaluate, adopting a comparative approach, the ventilation performance of a morphological family of buildings and to choose the shape of the building, its orientation and the position of the openings. In particular we focus on the interaction between the shape of the building and the wind, that produces a pressure distribution over the building's envelope, activating an internal airflow through the openings. The pressure difference between any two points lying on the envelope is considered as the force driving of the natural ventilation that depends mainly on the aspect ratio of the building (r) and of its orientation (α). Changing r and α in a specific range, we represent some different configurations. Then we reduce the problem from 3D to 2D, studying the airflow around the vertical and the horizontal cross-section of the building. By knowing the pressure values, we create some plots useful for the positioning of the openings and we calculate an indicator, measuring the global performance of ventilation of the building. By plotting the indicator of the ventilation potential, it is possible to compare the performance of a morphological building family. The graphics can be used by designers without any particular skills in aerodynamics.